Effectiveness of PBB-P2 Revenue Contribution, BPHTB and Hotel Tax on Cirebon City PAD: Pre and Post Covid-19 - Purnamawati, Rd Isnaeni; Arifin , Zaenal (Maksi, 2024)
One of the cities in Indonesia affected by Covid-19 is Cirebon City. Based on data from the Cirebon City Central Statistics Agency (BPS), Cirebon City's PAD revenue experienced a drastic decline in 2020 and 2021. Regional taxes that contribute to increasing Regional Original Income (PAD) include Rural and Urban Land and Building Taxes ( PBB P2), Land and Building Rights Acquisition Fee (BPHTB) and Hotel Tax. All three have great potential for development. The aim of this research is to find out and analyze the effectiveness of the contribution of PBB-P2, BPHTB, Hotel Tax revenues to Cirebon City PAD before and during the Covid-19 pandemic. This research uses a comparative research method with quantitative descriptive analysis techniques based on data from the 2018-2021 Target Report and Realization of Regional Original Revenue. The results of this study show that there are differences in the influence between the 3 variables tested, namely as follows: there is no visible relationship between the Hotel Tax variable and Original Regional Income, while the BPHTB and PBB-P2 variables have quite a large impact on Original Regional Income.